PENGARUH DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA KANTOR CAMAT MATARAM - Alhamida, Herlina; Sri Wahyulina (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the influence of work discipline and organizational culture on employee productivity at the Mataram Subdistrict Office. This study employs a quantitative approach using a census method involving all 70 employees. Data collection techniques included questionnaires, interviews, and documentation, while data analysis utilized multiple linear regression with the aid of SPSS. The results indicate that work discipline has a positive and significant effect on employee productivity (β = 0.615; t = 10.067; p < 0.05). Organizational culture also has a positive and significant effect on employee productivity (β = 0.386; t = 6.322; p < 0.05). Simultaneously, work discipline and organizational culture have a significant effect on employee productivity (F = 378.685; p < 0.05). The coefficient of determination (R² = 0.919) indicates that 91.9% of the variation in employee productivity can be explained by work discipline and organizational culture, while 8.1% is influenced by other factors outside the research model. These findings confirm that work discipline is the dominant factor in improving employee productivity, followed by organizational culture, which further reinforces work behavior. Therefore, strengthening discipline and consistently internalizing organizational culture are important strategies for improving performance and the quality of public services at the Mataram Subdistrict Office.